Features of Linguistic and Cultural Type “Bureaucrat”: Compatibility of Adjective bureaucratic - S. A. Anokhina; N. V. Pozdnyakova (Научный диалог, 2020)
The article is devoted to the analysis of the linguistic and cultural type “Russian bureaucrat”. The compatibility of the adjective bureaucratic is investigated according to the texts of the XIX - XXI centuries included in the National corpus of the Russian language. The novelty of the study is that to describe the character traits of the linguocultural type “Russian bureaucrat”, the authors refer to the compatibility of an adjective derived from the character type. It is noted that the connotative component in the meaning of the adjective determines an almost exclusively negative interpretation of the image: the pejorative component of the value determines the compatibility of the studied adjective with the designations of negative qualities. The authors dwell on the ideas that have developed in the Russian linguistic consciousness about the character of the Russian bureaucrat, and trace their transformations over two centuries. The analysis of the compatibility of the adjective showed that the linguistic and cultural character “Russian bureaucrat” is characterized by indifference, ignorance, cowardice, arrogance, insincerity. The authors of the article conclude that in the Russian language picture of the world indifference and cowardice are attributed to bureaucrats of different periods of Russian history, while ostentatious arrogance is noted mainly in the descriptions of officials of the past, and markers of ignorance and insincerity are more frequent in the characteristics of modern officials.